2005
DOI: 10.1177/0957926505056663
|View full text |Cite
|
Sign up to set email alerts
|

Staging insults and mobilizing categorizations in a multiethnic peer group

Abstract: This study explores how pre-adolescent boys of immigrant and working-class backgrounds stage insults and, as part of this process, mobilize categorizations. Data are drawn from ethnographic research combined with detailed analysis (conversation analysis and membership categorization analysis) of video records from peer interactions in an elementary school in Sweden. It was found that the boys deploy multiple resources (of syntactic and phonetic shapes) provided by the talk of the prior speaker and the turn str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 27 publications
5
103
0
6
Order By: Relevance
“…In line with previous research which has suggested that humorous teasing is an important aspect of male identity construction (Evaldsson, 2005b;Haugh & Bousfield, 2012;Schnurr & Holmes, 2009), the staff members and youths were found to orient toward teasing and the importance of being able to "take it"; responding to a tease without being overly aggressive. But the study also suggested that some instances could be conceptualized as rebellious humor in that some youths were successful in teasing or mocking the staff members.…”
Section: Study Ii: Teasing Laughing and Disciplinary Humor: Staff-yosupporting
confidence: 66%
See 1 more Smart Citation
“…In line with previous research which has suggested that humorous teasing is an important aspect of male identity construction (Evaldsson, 2005b;Haugh & Bousfield, 2012;Schnurr & Holmes, 2009), the staff members and youths were found to orient toward teasing and the importance of being able to "take it"; responding to a tease without being overly aggressive. But the study also suggested that some instances could be conceptualized as rebellious humor in that some youths were successful in teasing or mocking the staff members.…”
Section: Study Ii: Teasing Laughing and Disciplinary Humor: Staff-yosupporting
confidence: 66%
“…While this study, along with many others (for example, Antaki & Kent, 2012;Aronsson & Gottzén, 2011;Evaldsson, 2005b;Cromdal & Osvaldsson, 2012;Goodwin, 1990;Hepburn & Potter, 2011), upholds the value of using video recordings as data, specifically of so-called "naturally occurring" events (those that would most likely have happened even without the researcher's presence), this does not imply that video-recorded interaction here is assumed to be more "real" or "natural" than other data, at least not in the sense that it is somehow unaffected by my presence and the video camera's. Duranti (1997) has discussed "the participant-observer paradox," that is, the fact that the researcher must observe the interaction he or she wants to study, and that through observing interaction, the researcher will inevitably affect it (unless the researcher uses covert observation, which is ethically questionable) (1997, p. 118).…”
Section: Methodological Reflectionsmentioning
confidence: 99%
“…Evaldsson and Cekaite (2010) examined peer interactions in monolingual Swedish educational settings and showed how minority language children engaged in corrective practices that targeted others' faulty Swedish, thereby co-constructing the prevalent societal monolingual ideology (see also Cekaite & Björk-Willén, 2013). Moreover, Evaldsson (2005) shows that children oriented to the hierarchical value of majority language by resisting others' criticism of their Swedish language skills and the categorization as not fully competent in Swedish.…”
Section: Research On Language Practices and Parents' Strategies In Bimentioning
confidence: 99%
“…Such terms were used during character contests (Goffman 1967: 237). Evaldsson (2005) closely examines the sequential environments in which multiparty consensus (see also Evaldsson 2002;Goodwin 1990) is created to ratify particular depictions, tluough upgrades, laughter, recycles, repetitions, new linked evaluations, and so on that frame the acts of the offending party as disgusting. Evaldsson' s point is that we cannot ascribe meaning to members' categories without conducting extended fieldwork.…”
Section: Ritual Insult and Negative Assessmentsmentioning
confidence: 99%
“…Children make category-bound ac transgressors. Neg girls' groups, incb behind people's be (not having Po kerr generally), having being labeled a 'G in school) were r immigrant backg (Evaldsson 2005: ;1967: 237 rhyming references with 'ambiguous sexual irmuendo' (Mendoza-Denton 2008: 188); for example, Guera, guera, LQuien te encurea? ('Blondie, Blondie, who'll disrobe you?')…”
Section: Ritual Insult and Negative Assessmentsmentioning
confidence: 99%